SOCIO-ECONOMIC IMPACT OF SELF-HELP GROUPS ON WOMEN IN BIHAR: A SOCIOLOGICAL STUDY OF JEEVIKA SELF-HELP GROUP (International Journal of Food and Nutritional Sciences, 2023)
This sociological study investigates the profound socio-economic impact of Self-Help Groups (SHGs) on women in Bihar, focusing on the JEEViKA initiative. JEEViKA, launched in 2006, seeks to empower rural women by mobilizing them into SHGs, thereby fostering economic independence and social inclusion. The study explores the multifaceted changes experienced by women, encompassing aspects of self-development, economic stability, social dynamics, and overall empowerment. Through a comprehensive examination of JEEViKA’s sociological dimensions, the research aims to provide valuable insights into the transformative role of SHGs in shaping the lives of women in Bihar.